2010
DOI: 10.1177/0163443709356142
|View full text |Cite
|
Sign up to set email alerts
|

Promises unfulfilled? ‘Journalism 2.0’, user participation and editorial policy on newspaper websites

Abstract: The ideology surrounding Web 2.0 has been increasingly studied in a critical perspective (Zimmer, 2008). At the same time, several works have begun to give empirical results about the effective uses of Web 2.0 services, particularly online interactions on social networking sites (Aguiton and Cardon, 2007;Boyd and Ellison, 2007). In this article, we try to achieve both an ideological deconstruction and an empirical observation of a particular segment of Web 2.0. We will focus on digital journalism, a profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…This so called Crowdsourcing, is a major challenge, which needs a different perspective on citizens. It is necessary to change the perspective from content consumers to content producers (prosumers) [36,37,38,39]. In most cases, this change is difficult.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This so called Crowdsourcing, is a major challenge, which needs a different perspective on citizens. It is necessary to change the perspective from content consumers to content producers (prosumers) [36,37,38,39]. In most cases, this change is difficult.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among these are, first of all, the actual features of audience participation journalism provides (e.g. Domingo et al 2008;Thurman 2008;Rebillard & Touboul 2010;Hermida 2011). These consist of the different venues and channels to interact with journalists, ranging from, for example, letters to the editor and dedicated phone hotlines to E-mail, blogs, discussion boards or Twitter accounts.…”
Section: A Heuristic Model Of Inclusionmentioning
confidence: 99%
“…However, some recent studies (e.g. Hermida, 2010;Rebillard and Touboul, 2010) suggest that such tendencies might come to be challenged by new means of news production, distribution, and consumption. In sum, while the research results reported earlier span more than a decade, most findings still indicate that media practitioners in general tend to be closer to the notion of online journalism as "TV news on a computer screen" (Dahlgren 1996, 64), rather than the radical change some critics and pundits have proclaimed.…”
Section: Journalist Attitudes Toward Interactivitymentioning
confidence: 99%